Clearcutting the Pacific rain forest : production, science, and regulation - Rajala, Richard, 1953- (UBC Press, 1998)
"In Clearcutting the Pacific Rain Forest, Richard A. Rajala explores the roots of the deforestation crisis in the Douglas fir regions of British Columbia, Washington, and Oregon between 1880 and 1965. Beginning with a labour process analysis of the technological and managerial innovations that introduced a factory regime to coastal logging, the book goes on to study the environmental, scientific, and political history of clearcutting. Rajala documents the growing awareness of the impact of cutting practices on forest renewal and the development of silvicultural regulations in the American and Canadian contexts. Rajala's analysis of the relationship between governments and corporations in policy making suggests that regulatory initiatives served corporate rather than social or ecological ends." "By integrating class, environmental, and political issues, Rajala provides a unique perspective on the controversy surrounding clearcutting and other forest practices. Clearcutting the Pacific Rain Forest will be of exceptional worth to anyone interested in the social and ecological impact of technology and corporate structure, the development of forestry policy, and the plight of timber-dependent communities in the Pacific Northwest."--Jacket